2015
DOI: 10.1007/s10096-015-2312-2
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of Blastocystis sp. in active ulcerative colitis patients

Abstract: Ulcerative colitis (UC) is thought to originate from a disbalance in the interplay between the gut microbiota and the innate and adaptive immune system. Apart from the bacterial microbiota, there might be other organisms, such as parasites or viruses, that could play a role in the aetiology of UC. The primary objective of this study was to compare the prevalence of Blastocystis sp. in a cohort of patients with active UC and compare that to the prevalence in healthy controls. We studied patients with active UC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Notably, controversy exists to whether certain protozoa such as Blastocystis species may be more prevalent in healthy individuals and linked to certain beneficial health indices. 22 , 23 For now, however, our data are consistent with the findings of diverse pathogens reported by others 14 , 15 and support the current broad-spectrum screening approach for pathogens.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, controversy exists to whether certain protozoa such as Blastocystis species may be more prevalent in healthy individuals and linked to certain beneficial health indices. 22 , 23 For now, however, our data are consistent with the findings of diverse pathogens reported by others 14 , 15 and support the current broad-spectrum screening approach for pathogens.…”
Section: Discussionsupporting
confidence: 92%
“…has been considered as a potential pathogen associated with irritable bowel syndrome [IBS] (Poirier et al, 2012 ; Nourrisson et al, 2014 ) and inflammatory bowel diseases [IBD] (Petersen et al, 2013 ). However, it appears to be more common in the gut of healthy individuals compared to those with gut disease, and it is now by many considered a commensal (Petersen et al, 2013 ; Scanlan and Stensvold, 2013 ; Parfrey et al, 2014 ; Krogsgaard et al, 2015 ; Rossen et al, 2015 ; Stensvold and van der Giezen, 2018 ; Mardani Kataki et al, 2019 ; Tito et al, 2019 ). Moreover, Blastocystis sp.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Blastocystis is commonly detected in the gut of asymptomatic humans, and it has been shown that colonization is stable over 6-10 years [16,17]. It was shown that Blastocystis was more frequent in healthy subjects compared to subjects with IBD, pointing out a possible protective effect of its colonization [18][19][20]. It is known that the gut microbial communities include protozoa, fungi, bacteria, and viruses, which share the same environment and live in close relationship.…”
Section: Introductionmentioning
confidence: 99%